Sports and the rule of reason - Ragazzo, Carlos Emmanuel Joppert (Revista do IBRAC, 2025)
Litigation involving sports has no ordinary solution. It is widely known that one can easily envision a great philosophical discussion as to whether there should be any special legal treatment to sports-related claims. And antitrust violations in the sports contexts are no different; they have frequently troubled the courts with puzzling questions yet to be finally decided.